KONTRIBUSI KETERAMPILAN MENYIMAK BERITA TERHADAP KETERAMPILAN MENULIS TEKS BERITA SISWA KELAS IX SMP NEGERI 30 PADANG - Kharomah, Wahidiana Siti; Nursaid, Nursaid; Zulfikarni, Zulfikarni (Universitas Negeri Padang, 2018)
This article was written to describe the contribution of listening skills to news text on the skills of writing news text of students of class IX SMP Negeri 30 Padang. This research is a quantitative research with descriptive method. The sample in this study amounted to 40 people. The data of this research is score of skill test result of news news. Based on data analysis and discussion, the following three things are obtained. First, the skill of writing the news text of the students of class IX SMP Negeri 30 Padang is in good qualification (79.17). Secondly, the listening skill of news text news of class IX students of SMP Negeri 30 Padang is in good qualification (82,56). Third, the news listening skills have contributed 14.21% to the writing skills of news text of the students of class IX SMP Negeri 30 Padang and the rest (85.79%) influenced by other factors not examined in this study.Â Kata kunci: Kontibusi; Keterampilan Menyimak; Keterampilan Menulis; Teks BeritaÂ